Linguistic inputs in mothers of children with intellectual disabilities - Quintero Uribe, Jhon Fredy (Revista de Investigación en Logopedia, 2019)
In the second half of the 20th century, studies were developed out in different countries about the influence of the communicative style of parents in the development of language in children. These studies posed different positions regarding the quality of the inputs, which could be optimal or deficient. The objective of the study was to identify the linguistic inputs used by a group of mothers of children with intellectual disabilities. A documentary research was made, analyzing audiovisual records of communicative interactions between mothers and children in natural situations were analyzed. The children presented a clinical diagnosis, some of Down syndrome and others of Cerebral Palsy, and secondary to these diagnoses, intellectual disability. The information was processed through a qualitative analysis tool.
Keywords: Linguistic input; intellectual disability; language development